Lilywanag: A feasibility study on introducing an eco-friendly leather shiner product derived from water lily - Brylle Jerome T. Bagasiao, Jessca Marl M. Europeo, Erika Eunice B. Huliganga, Alessandro Renae C. Mabaquiao, Cristar C. Oredina, Karl Christian G. Roque 4 0 16; 5
u
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2